Effect of oil palm boiler ash on growth and yield of TR8 rice variety planted on acid sulphate soil - Armeylee Joneer; Kuang Cheong Tew; Mok Sam Lum (ANSI net, 2025)
Background and Objective: Rice production in Kota Belud, Sabah (Sabahʼs rice bowl), is challenged by highly acidic soil (3.68 pH). The ideal rice growth requires a pH between 5.5 to 6.5. This study aims to determine the optimal oil palm boiler ash rates for improving soil pH and enhancing the growth and yield of TR8 rice. Materials and Methods: The study involved a soil incubation with 12 treatments and 3 replications, using different oil palm boiler ash rates (0 to 50 ton/ha). Soil pH was measured at 10 day intervals over 60 days. Based on the incubation results, 5 ash rates (20-50 ton/ha) were selected for a pot experiment with TR8 lowland rice, using 6 treatments and 5 replications. Data were analyzed with ANOVA, LSD (p<0.05) and Pearson correlation to examine relationships between variables. Results: Application of 50 ton/ha oil palm boiler ash recorded the highest chlorophyll content (26.98), tiller number per hill (23.40) and yield per pot (795.15 g/m2 ). On the other hand, the application of 40 ton/ha oil palm boiler ash recorded the highest percentage of filled grain (88.69%) and the panicle number (23). In addition, the control (without oil palm boiler ash application) recorded the highest flag leaf length (38.22 cm). There was a strong positive correlation between yield per pot and number of panicles. This study showed that oil palm boiler ash at 50 ton/ha increased the soil pH to 6.29 potentially improving vegetative growth and increasing the yield of TR8 lowland rice. Conclusion: While, this study shows promise for using oil palm boiler ash to improve rice production in acidic soils, particularly for the TR8 rice variety, further field research is crucial to explore the effects on different soil types and rice varieties under field conditions.